Charge transfer driven by redox dye molecules on graphene nanosheets for room-temperature gas sensing. Issue 44 (3rd November 2021) - Liu, Wenbo; Zeng, Junwei; Gao, Yixun; Li, Hao; Rooij, Nicolaas Frans de; Umar, Ahmad; Algarni, Hamed; Wang, Yao; Zhou, Guofu
Abstract : Special functional groups to modify the surface of graphene have received much attention since they enable the charge transfer enhancement, thus realizing gas-sensing at room temperature. Abstract : Special functional groups to modify the surface of graphene have received much attention since they enable the charge transfer enhancement, thus realizing gas-sensing at room temperature. In this work, three typical redox dye molecules, methylene blue (MB), indigo carmine (IC) and anthraquinone-2-sulfonate (AQS), were selected to be supramolecularly assembled with reduced graphene oxide (rGO), respectively. Remarkably, three graphene-based materials AQS-rGO (response = 3.2, response time = 400 s), IC-rGO (response = 4.3, response time = 300 s) and MB-rGO (response = 7.1, response time = 100 s) exhibited excellent sensitivity and short response time toward 10 ppm NO2 at room temperature. The corresponding NO2 sensing mechanism of the obtained materials was further investigated by cyclic voltammetry (CV) measurements. CV was conducted to measure the anodic peak potential ( E pa ) of three redox dyes. Interestingly, it is obvious that the E pa values were positively correlated with the gas sensitivity and response time of the three materials. To explore the mechanism, UV–vis spectroscopy was adopted to analyze the lowest unoccupied molecular orbitals (LUMOs) of three redox dye molecules. The results show that the oxidation abilities of three redox dyes were also positively correlated with the gas sensitivity and response time of three corresponding graphene-based materials.